Is Readiness to Change Drinking Related to Reductions in Alcohol Use and Consequences? A Week-to-Week Analysis - Merrill, Jennifer E. (J Stud Alcohol Drugs, 2015)
OBJECTIVE: The literature on whether readiness to change (RTC) alcohol use translates into actual change among college students is both limited and mixed, despite the importance of understanding naturalistic change processes. Few studies have used fine-grained, prospective data to examine the link between RTC and subsequent drinking behavior, and alcohol consequences in particular. The present study involves tests of whether (a) intraindividual changes in RTC are negatively associated with alcohol use and alcohol-related consequences from week to week, (b) the effect of RTC on use and consequences is direct versus mediated by change in alcohol use, and (c) the association between RTC and drinking behavior is moderated by gender. METHOD: Participants were 96 college student drinkers who completed a baselinesurvey and 10 weekly web-based assessments of RTC, alcohol use, and consequences. RESULTS: Hierarchical linear models indicated that, as hypothesized, reporting greater RTC on a given week (relative to one’s average level of RTC) was negatively associated with alcohol use (measured by either drinks per week or frequency of heavy episodic drinking) and alcohol consequences the following week. Changes in use fully mediated the relationship between RTC and consequences. The prospective association between RTC and both alcohol use and consequences did not differ by gender. CONCLUSIONS: Findings suggest that higher RTC translates into short-term reductions in alcohol use and in turn alcohol consequences, and highlight important avenues for future research.